Persepsi Karyawan pada CSR, Keterlibatan Karyawan, dan Kepemimpinan Etis pengaruhnya terhadap Kreatifitas Karyawan - Boy Eduard Richard Wajong; Dadang Irawan; . Wylen; Innocentius Bernarto (Universitas Sam Ratulangi, 2020)
This paper examines the effect of employee engagement, employment perception of CSR, ethical leadership on employeeâ€™s creativity. It is believed that employeeâ€™s creativity will enhance productivity. This research is conducted in 2 MSG (Monosodium Glutamate) companies in Jakarta. The study showed that the employees were resilience, enthusiastic, and were also proactive. This research used sample data collection as a means of data gathering. The data were analyzed by partial least square-structural equation modelling (PLS-SEM) to test all the hypotheses. Eighty-five employees have claimed that there are positive effects from employee engagement, employee perception of CSR, ethical leadership towards employee creativity. This paper will also offer concepts into the practical implications of employee creativity, as well as the limitation and future directions for future research.Â